2003
DOI: 10.2174/1568009033481949
|View full text |Cite
|
Sign up to set email alerts
|

The MYC Oncogene as a Cancer Drug Target

Abstract: The universal deregulation of c-myc gene expression in tumor cells suggests that this oncogene represents an attractive target for cancer therapeutic purposes. The same applies to the N-myc gene, which has a more restricted tissue specificity. Translocation (e.g., c-myc in Burkitt's lymphoma), or amplification (e.g., N-myc in neuroblastoma) of myc genes has been causally linked to tumor formation. Furthermore, the c-myc promoter integrates diverse mitogenic signalling cascades, which are constitutively activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 119 publications
(129 reference statements)
4
95
0
2
Order By: Relevance
“…In addition, expression of spermidine/spermine N 1 -acetyltransferase (SSAT) is negatively regulated by the KRAS oncogene, which is commonly mutated -and, as a result, aberrantly activated -in human colon cancer and other gastrointestinal of which is associated with the development of Burkitt's lymphoma and several epithelial cancers, in addition to colorectal cancer 28 . MYC encodes a transcription factor that is required for the proliferation of some normal cells, but when overexpressed leads to uncontrolled growth and cancer 29 Figure 1 | Polyamine metabolism in mammals. The metabolism of arginine, which is produced in the urea cycle, through the action of arginase, results in the production of ornithine (other details of the urea cycle are not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, expression of spermidine/spermine N 1 -acetyltransferase (SSAT) is negatively regulated by the KRAS oncogene, which is commonly mutated -and, as a result, aberrantly activated -in human colon cancer and other gastrointestinal of which is associated with the development of Burkitt's lymphoma and several epithelial cancers, in addition to colorectal cancer 28 . MYC encodes a transcription factor that is required for the proliferation of some normal cells, but when overexpressed leads to uncontrolled growth and cancer 29 Figure 1 | Polyamine metabolism in mammals. The metabolism of arginine, which is produced in the urea cycle, through the action of arginase, results in the production of ornithine (other details of the urea cycle are not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of polyamine have long been associated with proliferation, and recent experiments with genetically altered rodents have confirmed the important roles of these molecules in both normal and neoplastic growth 53 . basis for neoplasia in Burkitt's lymphoma 29 . Inappropriate expression of MYC in models of this disease results in inappropriate ODC expression and tumorigenic phenotypes, including increased proliferation and decreased apoptosis 30,31 .…”
Section: Box 1 | Polyamines In Normal Growth Development and Tissue mentioning
confidence: 99%
“…Deletion mutations in the c-myc 5'UTR, which are present in several Burkitt lymphomas (resulting from translocation of the c-myc gene), result in enhanced translation of the c-Myc mRNA (Saito et al, 1983;Darveau et al, 1985;Parkin et al, 1988;Carter et al, 1999;Willis, 1999). cmyc is implicated in several biological processes such as cell growth, proliferation and apoptosis (reviewed in Gartel and Shchors, 2003;Hermeking, 2003;Levens, 2003;Pelengaris and Khan, 2003). c-Myc is expressed ubiquitously during embryogenesis and in post-developmental tissues with a high proliferative capacity.…”
Section: C-mycmentioning
confidence: 99%
“…Human SWI/SNF activity is important for the transcriptional activation of many genes, including the proto-oncogene c-myc, which is transcriptionally upregulated in many forms of human cancer (8,9). Chromatin immunoprecipitation experiments in vivo have shown that hSWI/SNF is present on the active c-myc promoter in proliferating T cells, but not the inactive promoter in resting T cells (10).…”
mentioning
confidence: 99%